Communication Interventions for Families of Pre-School Deaf Children in the UK. (June 2015) - Rees, Rachel; Mahon, Merle; Herman, Rosalind; Newton, Caroline; Craig, Gordon; Marriage, Josephine
<x content-type="archive" xml:space="preserve">Abstract</x> UK professionals use a range of intervention approaches to promote communication development in pre-school deaf children by influencing the familys' interaction style. This investigation surveyed the approaches used and explored how these translated into specific practices. An online questionnaire was developed and reviewed by a panel of experts. Part 1 explored professional background and approaches used. Findings showed that the main approaches were: auditory verbal therapy, Hanen, 'Parent–child interaction therapy' (PCIT), and guidance from the Monitoring Protocol for deaf babies and children (GMP). Of the 158 professionals who completed Part 1, 142 used a combination of these approaches, with each approach selected at least ninety-three times. When participants were asked which approach or combination of approaches influenced their practice most strongly, over 25 per cent chose GMP (mainly teachers of the deaf) and over 25 per cent chose Hanen and/or PCIT (mainly speech and language therapists). Part 2, completed by 117 professionals, required participants to rate how frequently they suggested particular strategies to parents and how frequently they used particular methods to encourage parents to adopt those strategies. There was no evidence of an association between the approaches selected and methods used and very little evidence of an association between the approaches and strategies selected. Many professionals were recommending similar strategies and using similar methods but there was also some variation in practice. The overall findings suggest that future research comparing named approaches may be of less value than studies that seek to explore the potential effectiveness of particular strategies and methods.